COMPARATIVE ANALYSIS OF FOLATE CYCLE MARKERS IN PATIENTS WITH TYPE 2 DIABETES COMPLICATED BY DIABETIC NEPHROPATHY - Barno Kh. Shagazatova; Said K. Bakhadirov; Bakhtiyor R. Mamasodikov (Central Asian Journal of Medicine, 2024)
One of the most studied genetic factors in the context of DN is the methylenetetrahydrofolate reductase (MTHFR) gene, specifically the C677T polymorphism. This single nucleotide polymorphism (SNP) is associated with elevated plasma homocysteine levels, which are known to contribute to vascular damage and the progression of nephropathy in diabetic patients. Research consistently shows that the 677T allele, particularly in individuals with the homozygous form (TT genotype), significantly increases the risk of developing DN across various populations.